Translation of Cryobiological Techniques to Socially Economically Deprived Populations—Part 1: Cryogenic Preservation Strategies - Buriak, Iryna; Fleck, Roland; Goltsev, Anatoliy; Shevchenko, Nadiya; Petrushko, Maryna; Yurchuk, Taisiia; Puhovkin, Anton; Rozanova, Svitlana; Guibert, Edgardo; Robert, Maria Celeste; Juan de Paz, Leonardo; Powell-Palm, Matthew J.; et al. (J. Med. Devices., 2020)
Use of cold for preservation of biological materials, avoidance of food spoilage and to manage a variety of medical conditions has been known for centuries. The cryobiological science justified these applications in the 1960s increasing their use in expanding global activities. However, the engineering and technological aspects associated with cryobiology can be expensive and this raises questions about the abilities of resource-restricted low and middle income countries (LMICs) to benefit from the advances. This review was undertaken to understand where or how access to cryobiological advances currently exist and the constraints on their usage. The subject areas investigated were based on themes which commonly appear in the journal Cryobiology. This led in the final analysis for separating the review into two parts, with the first part dealing with cold applied for biopreservation of living cells and tissues in science, health care and agriculture, and the second part dealing with cold destruction of tissues in medicine. The limitations of the approaches used are recognized, but as a first attempt to address these topics surrounding access to cryobiology in LMICs, the review should pave the way for future more subject-specific assessments of the true global uptake of the benefits of cryobiology.
Keywords: cryobiology, preservation, cells, developing countries, low income countries, middle income, banking, blood, plants, seeds, cord blood, animal germplasm, reproductive medicine, tissue banking, new approaches